Analisis Keperawatan Kompres Hangat Aromaterapi Lavender pada Nyeri Sectio Caesarea RSUD I.A Moeis - Fhauzia Iin Iin Aldini; Pipit Feriani; Tri Wahyuni; Joanggi W.H (Pustaka Galeri Mandiri, 2026)
Postoperative pain is a common problem experienced by patients after sectio caesarea due to tissue damage and surgical incisions. Pharmacological pain management has the potential to cause side effects; therefore, safe and effective non-pharmacological alternatives are needed. One intervention that can be used is the combination of warm compresses and lavender aromatherapy, which has relaxing and analgesic effects.This study aims to analyze the effectiveness of the intervention in reducing pain intensity and improving patient comfort. The method used was a case study with a nursing process approach that included assessment, diagnosis, planning, implementation, and evaluation. Pain measurement was carried out using the Numeric Rating Scale (NRS) before and after the intervention. The results showed a decrease in pain intensity from moderate to mild levels. Patients appeared more relaxed, comfortable, and able to carry out activities gradually.